Tephra layers of in the quaternary deposits of the Sea of Okhotsk: Distribution, composition, age and volcanic sources. (15th December 2016) - Derkachev, Alexander N.; Nikolaeva, Nataliya A.; Gorbarenko, Sergey A.; Portnyagin, Maxim V.; Ponomareva, Vera V.; Nürnberg, Dirk; Sakamoto, Tatsuhiko; Iijima, Koiji; Liu, Yanguang; Shi, Xuefa; Lv, Huahua; Wang, Kunshan
Abstract: The fullest summary on composition, age and distribution of 23 tephra layers detected and investigated in the Okhotsk Sea Pleistocene-Holocene deposits is presented. Seven tephra layers are surely identified with powerful explosive eruptions of volcanoes of Kamchatka, Kurile and Japanese Islands. For them, the areas of ash falls including which weren't revealed earlier on the land are specified and established. It is estimated that explosive eruptions of volcanoes of the Kamchatka Sredinny Range were the sources for three tephra layers. Complex investigations of morphological, mineralogical and chemical composition of tephras including composition of rare and earth-rare elements (electron microprobe analysis and laser ablation method - LA ICP MS) have been made for all studied layers. They were a basis for tephrostratigraphic correlation of the regional deposits promoting to specification of stages of volcanic explosive activity in this region.